Chemical Communication between Heart Cells is Disrupted by Intracellular Renin and Angiotensin II: Implications for Heart Development and Disease - De Mello, Walmor C. (Frontiers in Endocrinology, 2015)
The finding that intracellular renin and angiotensin II (Ang II) disrupts chemical communication and impairs metabolic cooperation between cardiomyocytes induced by aldosterone,hyperglycemia and pathological conditions like myocardial ischemia is discussed. The hypothesis is presented that epigenetic changes of the renin angiotensin aldosterone system ( RAAS) are responsible for cardiovascular abnormalities including the expression of RAAS components inside cardiac myocytes (intracrine RAAS) with serious consequences including inhibition of electrical and chemical communication in the heart resulting in metabolic disarrangement and cardiac arrhythmias. Moreover, the inhibition of gap junctional communication induced by intracellular Ang II or renin can contribute to the selection of cellular patterns during heart development.